Preclinical ex-vivo Testing of Anti-inflammatory Drugs in a Bovine Intervertebral Degenerative Disc Model - Li, Zhen; Gehlen, Yannik; Heizmann, Fabian; Grad, Sibylle; Alini, Mauro; Richards, R. Geoff; Kubosch, David; Südkamp, Norbert; Izadpanah, Kaywan; Kubosch, Eva Johanna; Lang, Gernot (Frontiers in Bioengineering and Biotechnology, 2020)
Discogenic low back pain (LBP) is a main cause of disability and inflammation is presumed to be a major driver of symptomatic intervertebral disc degeneration (IDD). Anti-inflammatory agents are currently under investigation as they demonstrated to alleviate symptoms in patients having IDD. However, their underlying anti-inflammatory and regenerative activity is poorly explored. The present study sought to investigate the potential of Etanercept and Tofacitinib for maintaining disc homeostasis in a preclinical intervertebral disc (IVD) organ culture model within IVD bioreactors allowing for dynamic loading and nutrient exchange. Bovine caudal IVDs were cultured in a bioreactor system for 4 days to simulate physiological or degenerative conditions: (1) Phy - physiological loading (0.02-0.2 MPa; 0.2 Hz; 2h/day) and high glucose DMEM medium (4.5 g/L); (2) Deg+Tumor necrosis factor α (TNF-α) - degenerative loading (0.32-0.5 MPa; 5 Hz; 2h/day) and low glucose DMEM medium (2 g/L), with TNF-α injection. Etanercept was injected intradiscally while Tofacitinib was supplemented into the culture medium. Gene expression in the IVD tissue was measured by RT-qPCR. Release of nitric oxide (NO), interleukin 8 (IL-8) and glycosaminoglycan (GAG) into the IVD conditioned medium were analyzed. Cell viability in the IVD was assessed using lactate dehydrogenase and ethidium homodimer-1 staining. Immunohistochemistry was performed to assess protein expression of IL-1β, IL-6, IL-8, and collagen type II in the IVD tissue. Etanercept and Tofacitinib downregulated the expression of IL-1β, IL-6, IL-8, Matrix metalloproteinase 1 (MMP1), and MMP3 in the nucleus pulposus (NP) tissue and IL-1β, MMP3, Cyclooxygenase-2 (COX2), and Nerve growth factor (NGF) in the annulus fibrosus (AF) tissue. Furthermore, Etanercept significantly reduced the IL-1β positively stained cells in the outer AF and NP regions. Tofacitinib significantly reduced IL-1β and IL-8 positively stained cells in the inner AF region. Both, Etanercept and Tofacitinib reduced the GAG loss to the level under physiological culture condition. Etanercept and Tofacitinib are able to neutralize the proinflammatory and catabolic environment in the IDD organ culture model. However, combined anti-inflammatory and anabolic treatment may be required to constrain accelerated IDD and relieving inflammation-induced back pain.